Evolution of the pseudogap state in HTSC single crystals ReBa₂Cu₃O₇₋δ (Re=Y, Ho) doped with Al and Pr - Vovk, R.V.; Zavgorodniy, A.A.; Obolenskii, M.A.; Samoilov, A.V.; Biletskiy, Y.V.; Pinto Simoes, V.M. (Functional Materials, 2009)
Studied has been the effect of oxygen deficiency as well as of a low (up to 5 %) Al and Pr doping on conductivity in the basis plane of the ReBa₂Cu₃O₇₋δ (Re=Y, Ho) HTSC single crystals. The excess conductivity Δσ(T) of the studied samples has been found to show an exponential character in a wide temperature range Tf<T<T*. The description of the excess conductivity as Δσ~(1-T/T*)exp(Δ*ab/T) can be interpreted within the frames of medium field theory where T* is the mean field temperature of superconducting transition. The temperature dependence of the pseudogap can be satisfactorily described in terms of the BCS-BEC crossover theoretical model. The oxygen content reduction and a low Al doping results in widening of the temperature interval where the PG mode is realized, thus narrowing the area of linear ρ(Т) dependence in the ab plane. A low Pr doping concentrations (z≈0.05) results in an unusual effect of a significant narrowing of temperature interval where the PG is realised, thus extending the linear ρ(Т) region.